INTERVENSI BALANCE STRATEGY EXERCISE LEBIH BAIK DALAM MENINGKATKAN KESEIMBANGAN DINAMIS DARIPADA ISOTONIC QUADRICEPS EXERCISE DENGAN BEBAN 1 KILOGRAM PADA LANSIA - Gusti Agung Gede Rama Wintara; I Putu Sutha Nurmawan; I Made Muliarta; I Putu Adiartha Griadhi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
Balance is an ability to maintain the center of gravity when stationary and when moving. An experimental study conducted with Pre and Post Test Two Group Design to compare Balance Strategy Exercise and Isotonic Quadriceps Exercise with a 1 kilogram load in improving dynamic balance for elderly aged over 60 years. A sample of 26 peoples divided into two groups. Independent Samples T-test found the average difference in improvement of dynamic balance in Balance Strategy group was 6,00 and the Isotonic Quadriceps group was 2,69 with p=0,000 (p<0,05). BalanceStrategy Exercise can be summed better in improving dynamic balance rather than Isotonic Quadriceps with a load of 1 kilogram in elderly aged over 60 years at Pitra Village, Penebel District, Tabanan. Keywords: Dynamic Balance, Balance Strategy Exercise, isotonic Quadriceps Exercise, Functional Gait Assessment